Indian special jurisdiction in Colombia: alternative use of law or pluralism? - Benavides-Burbano, Lilia Fernanda (Universidad Pedagógica y Tecnológica de Colombia, 2014)
Although the philosophical foundations of critical theory of law have more than a century, in recent years there have been various controversies regarding theories, which generally have common features, but also create confusion. This paper presents the special indigenous jurisdiction of Colombia that, by its principles, as it is explained in the development of this document, could be configured as an alternative use of the law, but for the author, it is a typical example of legal pluralism.